2021
DOI: 10.1101/2021.02.05.430003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralization of viruses with European, South African, and United States SARS-CoV-2 variant spike proteins by convalescent sera and BNT162b2 mRNA vaccine-elicited antibodies

Abstract: The increasing prevalence of SARS-CoV-2 variants with mutations in the spike protein has raised concerns that recovered individuals may not be protected from reinfection and that current vaccines will become less effective. The B.1.1.7 isolate identified in the United Kingdom and B.1.351 isolate identified in the Republic of South Africa encode spike proteins with multiple mutations in the S1 and S2 subunits. In addition, variants have been identified in Columbus, Ohio (COH.20G/677H), Europe (20A.EU2) and in d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
95
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 35 publications
12
95
0
3
Order By: Relevance
“…The obtained results are in line with previous studies reporting lowered NAb levels against B1.351 variant when compared to B1.1.7 or the older dominant strains 19,8,17,18,25 . Although previous studies have shown that pseudotype neutralization results have good concordance with SARS-CoV-2 neutralization assays 26 , it is necessary to have con rmatory data also using actual low-passage replicating clinical isolates that contain sets of mutations present in circulating strains.…”
Section: Main Textsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results are in line with previous studies reporting lowered NAb levels against B1.351 variant when compared to B1.1.7 or the older dominant strains 19,8,17,18,25 . Although previous studies have shown that pseudotype neutralization results have good concordance with SARS-CoV-2 neutralization assays 26 , it is necessary to have con rmatory data also using actual low-passage replicating clinical isolates that contain sets of mutations present in circulating strains.…”
Section: Main Textsupporting
confidence: 92%
“…The recently emerged variants of SARS-CoV-2 with phenotype affecting mutations in the RBD are of concern either due to increased transmissibility or because neutralization escape variants may lower the protective immunity of vaccinees and recoverees. Initial reports using small numbers of tested sera and a variety of techniques such as SARS-CoV-2 spike-variant pseudotyped lentivirus 17,18 or VSV 19 , infectious clones and virus isolates 20 have demonstrated differences in the levels of neutralizing activity of MAbs, convalescent patient and vaccinee sera. The trend in the results is, that the B.1.1.7-variant is neutralized nearly equally to the original virus type, whereas the B.1.351 variant is less well neutralized.…”
Section: Main Textmentioning
confidence: 99%
“…21 Reinfection rates following natural infection have not been shown to be higher in studies using SGTF as a proxy for B.1.1.7, 20,22 even though variably decreased sensitivity to neutralisation by monoclonal antibodies, convalescent plasma and sera from vaccinated individuals has been observed in vitro for B.1.1.7. [23][24][25][26][27][28][29][30][31][32][33][34] The Oxford-AstraZeneca trial showed good vaccine efficacy against sequencingconfirmed symptomatic B.1.1.7, despite evidence of decreased neutralising titres, but decreased efficacy for asymptomatic/unknown symptom infections. 35 Pfizer-BioNTech vaccine effectiveness in HCWs appears preserved despite increasing B.1.1.7 incidence in the UK; however these studies have not specifically investigated cases of SGTF or sequencing-confirmed B.1.1.7.…”
Section: Introductionmentioning
confidence: 99%
“…E484K was responsible for near complete resistance against multiple NTD and RBD mAbs and up to >10 and >30 times lower nAb titers in vaccinees and convalescent individuals, respectively. N501Y or K417N are additional mutations, all in RBD, conferring reduced nAb activity in SARS-CoV-2 vaccine and convalescent sera [292,293,296,297,[321][322][323][324][325][326][327][328]. These results could be recapitulated in experiments with SARS-CoV-2 isolates [329][330][331], whereas another study with recombinant SARS-CoV-2 carrying the specific point mutations reported smaller effects on nAb titers against infectious SARS-CoV-2 [332].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 87%
“…Some of these second-wave Spike mutations seem to confer partial neutralization resistance, as measured in in vitro assays with convalescent or vaccine sera [292][293][294][295][296][297]. Available potent vaccines at optimal dosing can induce multiple times higher nAb titers than convalescent sera [293,[298][299][300] and might thus have a broader window to compensate for partial Ab escape. The enrichment of second wave Spike variants (Table 2, Figure 6) suggests that Ab-mediated immunity, either obtained by SARS-CoV-2 infection or by vaccination, may have exerted critical selective pressure [80].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%